Risk parity: true versus naive approach - Alves, Gonçalo Filipe Abreu (2015)
This paper studies the performance of two different Risk Parity strategies, one from Maillard (2008) and a “naïve” that was already used by market practitioners, against traditional strategies. The tests will compare different regions (US, UK, Germany and Japan) since 1991 to 2013, and will use different ways of volatility. The main findings are that Risk Parity outperforms any traditional strategy, and the “true” (by Maillard) has considerable better results than the “naïve” when using historical volatility, while using EWMA there are significant differences.